2022
DOI: 10.1111/1759-7714.14422
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal “deep freeze”—transcarinal lymph node cryobiopsy

Abstract: Background: The diagnostic yield of endobronchial ultrasound-transbronchial needle aspiration (EBUS-TBNA) from mediastinal lymph nodes ranges from 66%-89%. However, in many cases cytologic material is not sufficient for full molecular evaluation. A novel method of transcarinal cryobiopsy aims to provide bronchoscopically obtained, larger specimen samples from mediastinal lymph nodes. We aimed to assess the efficacy and safety of transcarinal EBUS-guided lymph node cryobiopsy. Methods: Patients referred for EBU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…However, needle‐based specimens such as EBUS‐TBNA and EUS‐FNA are considered inadequate for immunostaining in many cases due to tissue volume, blood contamination, and crushing 5,6,12–14 . The addition of EBUS‐IFB or EBUS‐cryo to EBUS‐TBNA has been reported to have diagnostic utility, especially for lymphomas, uncommon tumors, and benign diseases 5–9 . A prospective study reported that only 46% of EUS‐FNA specimens for SMT were immunostainable, 13 and the diagnostic yield for SMTs was insufficient, ranging from 46% to 84%, 12–14 therefore biopsy methods for SMTs with high diagnostic rates need to be established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, needle‐based specimens such as EBUS‐TBNA and EUS‐FNA are considered inadequate for immunostaining in many cases due to tissue volume, blood contamination, and crushing 5,6,12–14 . The addition of EBUS‐IFB or EBUS‐cryo to EBUS‐TBNA has been reported to have diagnostic utility, especially for lymphomas, uncommon tumors, and benign diseases 5–9 . A prospective study reported that only 46% of EUS‐FNA specimens for SMT were immunostainable, 13 and the diagnostic yield for SMTs was insufficient, ranging from 46% to 84%, 12–14 therefore biopsy methods for SMTs with high diagnostic rates need to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Although its sensitivity and specificity are high for staging non‐small‐cell lung cancer, diagnostic yields for non‐cancer diseases are insufficient 1–6 . Recent studies have shown that adding EBUS‐guided intranodal forceps biopsy (EBUS‐IFB) or EBUS‐guided transbronchial mediastinal cryobiopsy (EBUS‐cryo) to EBUS‐TBNA provides higher diagnostic yields for lymphoma, uncommon tumors, and benign diseases compared to EBUS‐TBNA alone 5–9 …”
Section: Introductionmentioning
confidence: 99%
“…Here, clarifying the main reason for AS after EBUS‐TA was difficult; the involvement of the size of the tract created by EBUS‐TBNA and EBUS‐IFB cannot be ruled out. However, AS due to TS has not been reported, even in EBUS‐cryo, 9 , 10 which can help pass larger specimens through the tract than EBUS‐IFB. Therefore, we speculate that characteristics of CAC, which was poorly responsive to chemotherapy, were probably involved.…”
Section: Discussionmentioning
confidence: 99%
“…Endobronchial ultrasound (EBUS)‐guided tissue acquisition (TA) performed by transbronchial needle aspiration (TBNA) is the main diagnostic procedure for mediastinal and hilar lymphadenopathies given its safety and minimal invasiveness 1–6 . While EBUS‐TBNA has high sensitivity and specificity for diagnosing lymph node (LN) metastasis in lung cancer, 1,2 additional TA with EBUS‐TBNA, such as EBUS‐guided intranodal forceps biopsy (EBUS‐IFB) or EBUS‐guided cryobiopsy (EBUS‐cryo), can achieve higher diagnostic yields of lymphomas, uncommon tumors, and benign diseases, such as sarcoidosis 7–10 . EBUS‐IFB and EBUS‐cryo are advantageous as they can help obtain histological tissue samples 8,9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation